2019
DOI: 10.1111/btp.12731
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of intra‐annual population dynamics in a tropical soil arthropod

Abstract: Studies on inter‐annual dynamics of populations from temperate regions have shown that density dependence and climate effects are relatively common, albeit weak. Yet, for short‐lived organisms, intra‐annual variation may be at least as important. Furthermore, tropical species commonly experience temperatures close to their upper thermal limit and thus may be more likely to experience heat stress. Here, we used the soil mite Rostrozetes ovulum to investigate the drivers of intra‐annual population dynamics in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
(104 reference statements)
1
4
0
Order By: Relevance
“…Temperature affects ant thermoregulation, shaping thermal niches (Cerdá et al 1998;Cerdá and Retana 2000;Kaspari et al 2019) and also is related to species richness at larger scales (Dunn et al 2009). Indeed, we found that temperature had a direct effect on compositional dissimilarity, corroborating that even the low variation in temperature of the Amazon may affect the physiology of soil arthropods (Pequeno et al 2020). Nevertheless, temperature's greatest effect was indirect, through NDVI (b indirect = 0.74 × 0.36 = 0.27 vs. b direct = 0.17), which had the strongest direct effect among environmental variables (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Temperature affects ant thermoregulation, shaping thermal niches (Cerdá et al 1998;Cerdá and Retana 2000;Kaspari et al 2019) and also is related to species richness at larger scales (Dunn et al 2009). Indeed, we found that temperature had a direct effect on compositional dissimilarity, corroborating that even the low variation in temperature of the Amazon may affect the physiology of soil arthropods (Pequeno et al 2020). Nevertheless, temperature's greatest effect was indirect, through NDVI (b indirect = 0.74 × 0.36 = 0.27 vs. b direct = 0.17), which had the strongest direct effect among environmental variables (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Litter supply increases oribatid mite populations in tropical forests (Ashford et al, 2013; Pequeno et al, 2020), and thus can be expected to increase the effective population size of species. Therefore, stronger selection for sex with increasing litter amount agrees with linkage‐based advantages of sexual reproduction, which should increase in effectively larger populations (mechanisms 1, 2 and 3 in Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Litter supply increases oribatid mite populations in tropical forests (Ashford et al, 2013;Pequeno et al, 2020), and thus can be expected to increase the effective population size of species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, they have been mainly applied to vertebrates (e.g. Waddle et al 2015;Hamilton et al 2019) and rarely to invertebrate species (Klarenberg and Wisely 2019;Pequeno et al 2020).…”
Section: Introductionmentioning
confidence: 99%